2014
DOI: 10.3109/07420528.2014.957305
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effectiveness of a split sleep schedule in sustaining sleep and maintaining performance

Abstract: Shift work is common in today's society, and is associated with negative health outcomes, and accidents and incidents. These detrimental effects can be primarily attributed to sleeping and working at an adverse circadian time. The aim of this study was to examine whether a split sleep schedule is as effective as a consolidated day shift or night shift schedule for maintaining performance and sustaining sleep. Fifty-three healthy male volunteers (mean ± SD age = 26.51 ± 4.07 years) underwent a randomized three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 34 publications
3
40
2
Order By: Relevance
“…Eight of the studies identified in this review used a within-subject's design (18,22,23,25,29,(36)(37)(38), ten a between-subject's design (17,24,26,27,30,31,34,35,39,40), and four employed a mixed within-and between-subjects design (19,28,32,33). Seventeen studies were field-based (17-19, 22, 24-32, 34-37) and five used laboratory simulations (23,33,(38)(39)(40).…”
Section: Schedules and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight of the studies identified in this review used a within-subject's design (18,22,23,25,29,(36)(37)(38), ten a between-subject's design (17,24,26,27,30,31,34,35,39,40), and four employed a mixed within-and between-subjects design (19,28,32,33). Seventeen studies were field-based (17-19, 22, 24-32, 34-37) and five used laboratory simulations (23,33,(38)(39)(40).…”
Section: Schedules and Participantsmentioning
confidence: 99%
“…Five studies examined 8 hours-on/8 hours-off roster schedules, all of which were conducted with Australian train drivers (22,25,29,36,37), five examined 6 hours-on/6 hours-off shift schedules, predominantly in ship bridge officers and offshore fleet workers (17,23,30,34,39), and nine examined 4 hours-on/8 hours-off shift schedules all among maritime watch keepers (17, 26-28, 30-33, 35). The remaining LWSW studies employed less common schedules.…”
Section: Schedules and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) did not adversely affect total sleep duration. In another simulated shift work study, split sleep was associated with reduced sleep efficiency as compared to consolidated sleep (Jackson et al, 2014). However, this effect becomes negligible under conditions of sustained sleep restriction (Mollicone et al, 2007), as is more typical in operational settings.…”
Section: Sleep Findingsmentioning
confidence: 91%
“…In the same context, Jackson et al (2014) split evenly into two sleep periods, with two conditions in which sleep was consolidated into a single period (either daytime consolidated sleep and or nighttime consolidated sleep), to determine the effects of the sleep patterns on sleep, performance and subjective state. Overall, participants in the nighttime and split sleep conditions obtained significantly more total sleep time than participants in the daytime sleep condition.…”
Section: Sleep Fatigue Performance and Alertnessmentioning
confidence: 99%